THE ISLAMIC PERSPECTIVE ON THE CONSTRUCTION OFACCOUNTING DISCIPLINE - Iwan Triyuwono (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
The study attempts to elaborate critically the construction of accounting discipline that is based on Islamic values, especially in the aspects of ontology and epistemology. The analysis of the study begins with discussing a debate of modernism and postmodernism. Under this discussion, it is argued that modern knowledge (for example, accounting) which is constructed based on modern methodology has philosophical weaknesses and is now attacked by postmodernism. The discussion of post modernism leads us to Islamic perspective of knowledge that is the future orientation of how Shari'ate (Islamic) accounting discipline should be constructed.